Physical Fitness Profiles Among National Powerlifters With Disabilities - Meera Abdullah, Nagoor; Appukutty, Mahenderan; Darus Abdullah, Muhamad; Parnabas, Vincent (Media Ilmu Keolahragaan Indonesia, 2013)
The aim of this study was to investigate the physical fitness profiles among the national powerlifters with disabilities. A total of eight national powerlifting athletes (3 females and 5 males) were recruited and performed 1-RM bench press test, 20-seconds wheelchair push-up test, 50-meter dash, handgrip strength test, and arm crank ergometer test. The mean value of 1-RM bench press test was 1.78 ± 0.58 with all of the subjects classified as above average. The mean for 20-seconds wheelchair push-up test was 26.00 ± 8.50 repetitions as 75% of the subjects were above average, 12.5% were average, while another 12.5% were below average. The results of 50-meter dash showed that the mean value was 17.35 ± 4.72 seconds. The mean for left handgrip strength test was 38.86 ± 12.95 kg while the mean for right handgrip strength was 37.12 ± 12.77 kg. About 25% of the subjects were above average, 50% were in average rank, while another 25% were below average for the left handgrip strength test. For the right handgrip strength, 12.5% classified as above average, 50% were average, and another 37.5% were below average. All of the subjects were able to finish an arm crank ergometer test as the mean value of the test was 100.50 ± 25.57 RPM. Based on results, muscular strength, power and muscular endurance reveals that subjects are within the range. The future research could incorporate body composition evaluation and anthropometric profiles among powerlifters with disabilities for better understanding of sporting performance.